Obtenção, caracterização e avaliação da estabilidade de extrato do urucum nanoencapsulado em goma do cajueiro - Aguiar, Nágela Martins Oliveira (2013)
Consumers demands for healthier eating are increasing, which has led the industry to invest more persistent in the use of natural products. One of more relevant segment is natural substances acting as pigments, replacing the artificial coloring. Due his high instability, several researches have been directed to determine favorable conditions of use of these substances. Among the compounds studied we have bixin, a natural pigment, carotenoid, lipid-soluble annatto seed extract (Bixa orellana L.). Most carotenoids are sensitive to factors such as high temperature, light, oxygen and low pH, which restricts its use as a pigment in some food products. The use of nanoencapsulation has been an alternative for improving the stability of pigments such as bixin, making possible its incorporation into food systems without loss of its qualities. Considering that, the present study aimed to obtain, characterize and assess the stability of nanocapsules containing annatto extract, employing the cashew gum as wall material. To obtain these nanocapsules were performed steps of preparation of the emulsion and spray drying. The nanocapsules were characterized and showed a average size of 24.17nm + 3.71 with distribution by volume of 97.33% + 2.08, demonstrating high degree of homogeneity in size. The solubility of the nanocapsules was 74.13% + 3.68 and the efficiency achieved in the process of nanoencapsulation was 44.74% + 4.38. Stability tests were made with nanocapsules storing them in conditions of absence and presence of light. During ten days, for forty days, was made the determination of colorimetric coordinates a*, b*, L*, C*, Hue angle and the determinations of the levels of total bixin and superficial bixin. The total bixin had a reduction of 78,48% for the nanocapsules exposed to light, while in condition of absence of light the reduction was only 41.88%. The values ​​of surperficial bixin or unencapsulated, ranged from 27.64 mg/100g to 8.65 mg/100g, for samples subjected to light, and from 27,64 mg/100g + 2,13 a 16,45 mg/100g + 0,80 for samples stored in absense of light. The nanocapsules showed greater stability when stored away from light, confirming the deleterious light effect in annatto extract and therefore not full protection of cashew gum as wall material. Were also found in this study the antioxidant activities (using the system β-caroteno/ acid linoleic) and antimicrobial (by disk diffusion) of nanocapsules containing annatto extract. In relation to the antioxidant activity (inhibition of the oxidation of β-carotene) was obtained average perceptual corresponding to 61.90%, 54.576%, and 51.73% for containing extracts of nanocapsule concentration of 40 mg/L, 30 mg/L and 20 mg/L. The results suggests antimicrobial activity of the nanocapsules, making an inhibition zone against Staphylococcus aureus using concentrations of 1 mg/L, 2 mg/L and 10 mg/L, however there was observed the formation of inhibition zones for Escherichia coli and Salmonella choleraesuis. In this study, nanocapsules containing annatto extract were applied to the model system (buffer) and food system (yogurt). The stability of these systems was measured using the colorimetric parameters, during five days, for 40 days. It was observed that the system model may have promoted the nanocapsule stability, retaining their nucleus. When applied in yoghurt gave the nanocapsules to this food yellow / orange coloration and during the storage period was reduced values ​​of a* and increased b* and C* parameters.